2019
DOI: 10.1186/s13017-019-0258-x
|View full text |Cite
|
Sign up to set email alerts
|

Early fixation versus conservative therapy of multiple, simple rib fractures (FixCon): protocol for a multicenter randomized controlled trial

Abstract: Background Multiple rib fractures are common injuries in both the young and elderly. Rib fractures account for 10% of all trauma admissions and are seen in up to 39% of patients after thoracic trauma. With morbidity and mortality rates increasing with the number of rib fractures as well as poor quality of life at long-term follow-up, multiple rib fractures pose a serious health hazard. Operative fixation of flail chest is beneficial over nonoperative treatment regarding, among others, pneumonia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Historically, rib fractures have been managed nonoperatively. Nonoperative treatment includes multimodal pain management, oxygen support or mechanical ventilation if required, and pulmonary physical therapy such as incentive spirometry (29). Even with improved critical care technology and widespread adoption of adjunctive pain management techniques, outcomes after multiple severe rib fractures have not significantly improved over the past 15 years (30).…”
Section: Review Articlementioning
confidence: 99%
“…Historically, rib fractures have been managed nonoperatively. Nonoperative treatment includes multimodal pain management, oxygen support or mechanical ventilation if required, and pulmonary physical therapy such as incentive spirometry (29). Even with improved critical care technology and widespread adoption of adjunctive pain management techniques, outcomes after multiple severe rib fractures have not significantly improved over the past 15 years (30).…”
Section: Review Articlementioning
confidence: 99%
“…Second, patients from the DISS were registered as having sustained one or multiple rib fractures where multiple was defined as 2 or more rib fractures. In current literature, multiple rib fractures are defined as having three or more rib fractures, regardless of side or adjacency [42,45,46]. Only for the HLOS, which was covered by the HDR, a third subgroup, patients with a flail chest, was available.…”
Section: ) Patientsmentioning
confidence: 99%
“…Once the effusion and blood clot have been removed, bronchoscopy can be used for sputum suction during open reduction and internal fixation, and the effect of pulmonary reexpansion can be observed under direct vision. A large number of clinical studies have demonstrated that, in cases of multiple rib fractures, treatment with internal fixation is superior to the conservative treatments used to prevent pulmonary complications like atelectasis [14][15][16][17][18][19].…”
Section: The Necessity Of Surgical Treatmentmentioning
confidence: 99%